Pengembangan Booklet Crustacea Pantai Ujung Patikalo Untuk Meningkatkan Hasil Belajar Kognitif: Development of a Crustacean Booklet Based on Ujung Patikalo Beach to Improve the Cognitive Learning Outcomes - Surya Karinanta Sembiring; Widya Arwita; Fauziyah Harahap (Al-Musannif, 2026)
Animalia learning in high schools is still dominated by general textbooks that rarely integrate local biodiversity, resulting in limited cognitive learning outcomes. This study aimed to develop a Crustacea Booklet of Ujung Patikalo Beach as a learning resource for Animalia and to evaluate its validity, practicality, and effectiveness. This Research and Development (R&D) study employed the 4D model (define, design, develop, and disseminate). The study involved six expert validators, one biology teacher, and two Grade X classes of SMA Negeri 1 Tukka as the experimental and control groups. Data were collected through observations, interviews, questionnaires, documentation, and cognitive achievement tests. The booklet was rated highly valid by experts (87.01–91.73%) and received very positive responses from the teacher and students (91.66–99.00%). The experimental class achieved a high N-Gain score (0.71), exceeding that of the control class (0.39). The Independent Sample t-test indicated a significant difference in cognitive learning outcomes between the two groups (p < 0.05). These findings demonstrate that the developed booklet is a valid, practical, and effective local potential-based learning resource for improving students’ cognitive learning outcomes in Animalia.